Genetic characterization of Guinea-Bissau using a 12 X-chromosomal STR system: Inferences from a multiethnic population. (November 2017) - Gomes, Iva; Pereira, Plácido J.P.; Harms, Sonja; Oliveira, Andréa M.; Schneider, Peter M.; Brehm, António
Highlights: Genetic characterization of a male population from Guinea-Bissau using a 12 X-chromosomal STR system. No significant differences ( F ST ) between 18 Guinean-Bissau ethnic groups detected. Over 100 DNA West African sequences provide new insights into the repeat sequence structure of the studied X-STRs. The genetic homogeneity of the West African region is further supported by the lack of significant differentiation with a population sample composed by other countries from West Africa. Abstract: A male West African sample from Guinea-Bissau (West-African coast) was genetically analyzed using 12 X chromosomal short tandem repeats that are grouped into four haplotype groups. Linkage disequilibrium was tested (p ≤ 0.0008) and association was detected for the majority of markers in three out of the four studied haplotype clusters. The sample of 332 unrelated individuals analyzed in this study belonged to several recognized ethnic groups (n = 18) which were used to evaluate the genetic variation of Guinea-Bissau's population. Pairwise genetic distances ( F ST ) did not reveal significant differences among the majority of groups. An additional 110 samples from other countries also belonging to West Africa were as well compared with the sample of Guinea-Bissau. No significant differences were found between these two groups of West African individuals, supporting the genetic homogeneity of this region on the X chromosome level. The generation of over 100 DNA West African sequences provided new insights into the repeat sequence structure of some of the present X-STRs. Parameters for forensic evaluation were also calculated for each X-STR, supporting the potential application of these markers in typical kinship scenarios. Also, the high power of discrimination values for samples of female and male origin observed in this study, confirms the usefulness of the present X-STRs in identification analysis.